Enabling full‐length evolutionary profiles based deep convolutional neural network for predicting DNA‐binding proteins from sequence. Issue 1 (8th July 2019) - Chauhan, Sucheta; Ahmad, Shandar
Abstract: Sequence based DNA‐binding protein (DBP) prediction is a widely studied biological problem. Sliding windows on position specific substitution matrices (PSSMs) rows predict DNA‐binding residues well on known DBPs but the same models cannot be applied to unequally sized protein sequences. PSSM summaries representing column averages and their amino‐acid wise versions have been effectively used for the task, but it remains unclear if these features carry all the PSSM's predictive power, traditionally harnessed for binding site predictions. Here we evaluate if PSSMs scaled up to a fixed size by zero‐vector padding (pPSSM) could perform better than the summary based features on similar models. Using multilayer perceptron (MLP) and deep convolutional neural network (CNN), we found that (a) Summary features work well for single‐genome (human‐only) data but are outperformed by pPSSM for diverse PDB‐derived data sets, suggesting greater summary‐level redundancy in the former, (b) even when summary features work comparably well with pPSSM, a consensus on the two outperforms both of them (c) CNN models comprehensively outperform their corresponding MLP models and (d) actual predicted scores from different models depend on the choice of input feature sets used whereas overall performance levels are model‐dependent in which CNN leads the accuracy.